2019
DOI: 10.32815/jitika.v13i2.346
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Modul Praktikum SPSS Versi 20 Pada Matakuliah Statistika Dan Probabilitas Berbasis WEB Untuk Memfasilitasi Keterampilan Pengujian Hipotesis Penelitian

Abstract: ABSTRACT. Instructional media is a major element of the active learning process. Active learning emphasizes the activities of students in accessing information from various sources, to be discussed in the learning process in the classroom, experiences that not only increase knowledge, but also the ability of analysis and synthesis. Students are required to play a more active role in developing independent learning methods, starting from planning, implementing and evaluating the learning process. The use of sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
0
1
0
1
Order By: Relevance
“…In addition, the results of this study on the development of statistical practicum books/modules using SPSS have been studied previously including [18], [19], and [20], the results of the study revealed that the textbooks/practicum modules developed were feasible to use for learning and were effective in improving student learning outcomes. In addition, the textbooks/practicum modules produced increase students' motivation and independence in learning.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, the results of this study on the development of statistical practicum books/modules using SPSS have been studied previously including [18], [19], and [20], the results of the study revealed that the textbooks/practicum modules developed were feasible to use for learning and were effective in improving student learning outcomes. In addition, the textbooks/practicum modules produced increase students' motivation and independence in learning.…”
Section: Discussionmentioning
confidence: 98%
“…Untuk dapat menganalisis data hasil pengamatan tersebut dengan seiringnya perkembangan ilmu pengetahuan dan teknologi tidak harus dikerjakan secara manual lagi akan tetapi dapat dilakukan dengan menggunakan paket software aplikasi untuk analisis statistika yang merupakan salah satu hasil dari perkembangan ilmu pengetahuan dan teknologi. Penelitian sejalan sebagaimana (Widyastuti, 2019) mengembangkan modul praktikum SPSS Versi 20 pada mata kuliah Statistika dan Probabilitas Berbasis Web untuk memfasilitasi keterampilan pengujian hipotesis penelitian dan (Munir, 2018) melakukan penelitian untuk mengembangkan petunjuk praktikum MATLAB dan menguji efektivitasnya pada mahasiswa semester IV Jurusan Pendidikan Matematika IAIN Mataram. SPSS merupakan salah satu program pengolahan data statistik terpopuler, berbagai analisis data statistik dapat dilakukan dengan mudah dan prosedur analisis data melalui interface yang sederhana (Tim W. K., 2012) (Rosadi, 2016).…”
Section: Pendahuluanunclassified
“…The lameshow sampling method is being used to collect data from the target group, which consists entirely of paying customers. Multiple regression analysis was performed using the statistical package SPSS version 20 (Widyastuti & Nurfarida, 2019). Price has a positive and significant impact on customer satisfaction (with a sig.…”
mentioning
confidence: 99%